Neuropilin-2 induced by transforming growth factor-β augments migration of hepatocellular carcinoma cells. Issue 1 (December 2015) - Wittmann, Philipp; Grubinger, Markus; Gröger, Christian; Huber, Heidemarie; Sieghart, Wolfgang; Peck-Radosavljevic, Markus; Mikulits, Wolfgang
Abstract Background Hepatocellular carcinoma (HCC) is the most common form of liver cancer and the third most lethal cancer worldwide. The epithelial to mesenchymal transition (EMT) describes the transformation of well-differentiated epithelial cells to a de-differentiated phenotype and plays a central role in the invasion and intrahepatic metastasis of HCC cells. Modulation of the transforming growth factor-β (TGF-β) signaling is known to induce various tumor-promoting and EMT-inducing pathways in HCC. The meta-analysis of a panel of EMT gene expression studies revealed that neuropilin 2 (NRP2) is significantly upregulated in cells that have undergone EMT induced by TGF-β. In this study we assessed the functional role of NRP2 in epithelial and mesenchymal-like HCC cells and focused on the molecular interplay between NRP2 and TGF-β/Smad signaling. Methods NRP2 expression was analyzed in human HCC cell lines and tissue arrays comprising 133 HCC samples. Cell migration was examined by wound healing and Transwell assays in the presence and absence of siRNA against NRP2. NRP2 and TGF-β signaling were analyzed by Western blotting and confocal immunofluorescence microscopy. Results We show that NRP2 is particularly expressed in HCC cell lines with a dedifferentiated, mesenchymal-like phenotype. NRP2 expression is upregulated by the canonical TGF-β/Smad signaling while NRP2 expression has no impact on TGF-β signaling in HCC cells. Reduced expression of NRP2 by knock-down or inhibition of TGF-β signaling resulted in diminished cell migration independently of each other, suggesting that NRP2 fails to collaborate with TGF-β signaling in cell movement. In accordance with these data, elevated levels of NRP2 correlated with a higher tumor grade and less differentiation in a large collection of human HCC specimens. Conclusions These data suggest that NRP2 associates with a less differentiated, mesenchymal-like HCC phenotype and that NRP2 plays an important role in tumor cell migration upon TGF-β-dependent HCC progression.